Lead (Pb) Accumulation in Water, Sediment and Mussels (Hiatula chinensis) from Pasir Panjang Coast, Lekok-Pasuruan - Yona, Defri; Andira, Andira; Sari, Syarifah Hikmah Julinda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
This study attempted to evaluate Pb accumulation in the water, sediment and mussels (Hiatula chinensis) from Lekok-Pasuruan. There were four sampling stations representing the study area: (1) urban areas, (2) water flow area from steam power plant (PLTU), (3) waste disposal area of PLTU, (4) fishing port. The average concentration of lead varied between stations in the water (0.279 ppm), sediment (0.423 ppm) and mussels (0.427 ppm). Pearson`s correlation test shows strong relationship (p > 0.05) between Pb in the water, sediment and Hiatula chinensis. Mussels accumulation of lead from the sediment was assessed using bio-concentration factor (BCF) and the result shows Hiatula chinensis is an accumulator of Pb (BCF > 1).